The new Yale book of quotations - Shapiro, Fred R.; Menand, Louis (Yale University Press, 2021)
Updated to include more than a thousand new quotations, this reader-friendly volume contains over twelve thousand famous quotations, arranged alphabetically by author and sourced from literature, history, popular culture, sports, digital culture, science, politics, law, the social sciences, and all other aspects of human activity. Contemporaries added to this edition include Beyoncé, Sandra Cisneros, James Comey, Drake, Louise Glück, LeBron James, Brett Kavanaugh, Lady Gaga, Lin-Manuel Miranda, Barack Obama, John Oliver, Nancy Pelosi, Vladimir Putin, Bernie Sanders, Donald Trump, and David Foster Wallace. The volume also reflects path-breaking recent research resulting in the updating of quotations from the first edition with more accurate wording or attribution. It has also incorporated noncontemporary quotations that have become relevant to the present day. In addition, The New Yale Book of Quotations reveals the striking fact that women originated many familiar quotations, yet their roles have been forgotten and their verbal inventions have often been credited to prominent men instead. This book's quotations, annotations, extensive cross-references, and large keyword index will satisfy both the reader who seeks specific information and the curious browser who appreciates an amble through entertaining pages.